2013
DOI: 10.7763/ijssh.2013.v3.212
|View full text |Cite
|
Sign up to set email alerts
|

Academic Burnout and Motivation of Chinese Secondary Students

Abstract: Abstract-The purpose of this study was to identify patterns of academic burnout in 730 Chinese middle school students, and to link the burnout patterns with academic motivation. Using cluster analysis, we identified four motivation groups: (a) distressed group, (b) persevering group, (c) laissez-faire group, and (d) well-functioning group. The results of optimal scaling procedures indicated that grade level and motivation variables (intrinsic and extrinsic motivation, and amotivation) were good discriminators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 26 publications
(26 reference statements)
8
34
2
4
Order By: Relevance
“…Given the composition of the clusters, the participants in the first cluster can be called distressed students and the students in the second cluster, wellfunctioning students. Previous research found a higher variability and distinguished four types of students, ranging from the highest to the lowest level of burnout (Zhang, Klassen, &Wang, 2013).The differences between the two groups of students regarding the components of learning motivation were statistically significant (Table 4). Convergent with the results of previous analyses, the Extrinsic goals scale was the only component without significant differences.…”
Section: Resultsmentioning
confidence: 76%
“…Given the composition of the clusters, the participants in the first cluster can be called distressed students and the students in the second cluster, wellfunctioning students. Previous research found a higher variability and distinguished four types of students, ranging from the highest to the lowest level of burnout (Zhang, Klassen, &Wang, 2013).The differences between the two groups of students regarding the components of learning motivation were statistically significant (Table 4). Convergent with the results of previous analyses, the Extrinsic goals scale was the only component without significant differences.…”
Section: Resultsmentioning
confidence: 76%
“…Until recently, studies on students' burnout have been limited to supervisory and advisory roles such as research and teacher assistants (3). Academic burnout among students comprises three components including feelings of tired-ness due to educational demands and requirements (exhaustion), pessimism and lack of interest in tasks (cynicism), and inadequacy as a student (inefficacy) (4). Academic burnout is a reaction to chronic stress due to academic requirements, caused by the discrepancy between students' performance and their expectations about their academic achievement (5).…”
Section: Introductionmentioning
confidence: 99%
“…Also, individuals with more serious PTSD symptoms may have fewer resources to meet their demands at work, and thus this situation predisposes them to experience burnout (Rojas-Flores et al, 2015). Because students’ core activities may be considered as a kind of ‘work’ (Shih, 2012; Zhang, Klassen, & Wang, 2013), we may speculate that PTSD symptom severity will be associated positively with academic burnout among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, although the unique role of PTSD symptom severity and control beliefs in burnout has been assessed (Baird & Jenkins, 2003; Glass & McKnight, 1996), no studies to date have examined their combined role in burnout, particularly in academic burnout among adolescents. Furthermore, the demand–resource model is considered to apply to various occupational settings (Bakker et al, 2005), for example, in academic settings, students’ core activities may be considered as a kind of ‘work’ (Shih, 2012; Zhang et al, 2013), and they also encounter many different study demands and resource situations, which may later be manifested in their level of burnout at school (Salmela‐Aro & Upadyaya, 2014). However, few studies have examined the application of this model in studies of student behaviour (Salmela‐Aro & Upadyaya, 2014).…”
Section: Introductionmentioning
confidence: 99%